2012
DOI: 10.1002/ppul.22599
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with the need for a tracheostomy in extremely low birth weight infants

Abstract: In an attempt to determine the risk factors associated with the need for a tracheostomy in extremely low birth weight (ELBW) infants, a retrospective, case control study was conducted (each infant with a tracheostomy [case] was matched to two controls). Medical records were reviewed for patients' characteristics, risk factors for tracheostomy and outcome. During the study period (June 1996 to Dec 2010), 934 ELBW infants were admitted to our institution and nine infants had a tracheostomy and were matched to 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
30
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 14 publications
6
30
1
Order By: Relevance
“…3,11 This is likely because we included all infants admitted to the NICU, and previous studies focused on low birth weight infants (<2500 g) or those with BPD. 5,6,11,12 In a single-center study including all infants regardless of diagnosis or GA, tracheostomy rate was still higher than our cohort at 1.8%. 3 The Pediatrix Clinical Data Warehouse, the data source for our study, represents a broad mix of NICUs of different acuity levels including academic medical centers and community hospitals, and may be a more accurate representation of the NICU population across the United States.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…3,11 This is likely because we included all infants admitted to the NICU, and previous studies focused on low birth weight infants (<2500 g) or those with BPD. 5,6,11,12 In a single-center study including all infants regardless of diagnosis or GA, tracheostomy rate was still higher than our cohort at 1.8%. 3 The Pediatrix Clinical Data Warehouse, the data source for our study, represents a broad mix of NICUs of different acuity levels including academic medical centers and community hospitals, and may be a more accurate representation of the NICU population across the United States.…”
Section: Discussioncontrasting
confidence: 64%
“…4-6 Data regarding tracheostomy and outcomes in other infant populations are limited, as are data on risk factors associated with outcomes following tracheostomy. The few existing studies evaluating risk factors include predominantly older children, focus on the postnatal age at tracheostomy, and report different clinical outcomes.…”
mentioning
confidence: 99%
“…Bronchopulmonary dysplasia is an independent risk factor that predicts a higher likelihood of 30‐day major complications for pediatric tracheostomy, regardless of weight. This result corroborates previously published results, which also show it to be the most common indication for neonatal tracheostomy . Indeed, approximately 20% of infants with BPD who are referred to regional neonatal intensive care units die or receive a tracheostomy before discharge from the neonatal intensive care unit .…”
Section: Discussionsupporting
confidence: 92%
“…The proportion of tracheostomized VLBWIs in Japan was comparable to those in previous studies . We verified that the rate did not increase during the study period.…”
Section: Discussionsupporting
confidence: 87%
“…They found that the proportion initially increased from 0.01% to 0.1% from 1997 to 2005 but remained relatively unchanged thereafter. Viswanathan et al reported that 9 (0.96%) of 934 low‐birth‐weight infants (LBWIs) required tracheostomies but that the proportion did not change markedly from 1996 to 2010. Notably, both reports showed the growing impact of BPD on the outcomes of tracheostomy, along with multiple intubations, the duration of mechanical ventilation and non‐congenital upper airway obstruction.…”
Section: Discussionmentioning
confidence: 99%